2019
DOI: 10.3390/ijms20133215
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Action under Metal/Metalloid Stress: Regulation of Biosynthesis, Metabolism, and Molecular Interactions

Abstract: Polyamines (PAs) are found in all living organisms and serve many vital physiological processes. In plants, PAs are ubiquitous in plant growth, physiology, reproduction, and yield. In the last decades, PAs have been studied widely for exploring their function in conferring abiotic stresses (salt, drought, and metal/metalloid toxicity) tolerance. The role of PAs in enhancing antioxidant defense mechanism and subsequent oxidative stress tolerance in plants is well-evident. However, the enzymatic regulation in PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 121 publications
2
40
0
Order By: Relevance
“…Further, we investigated only three key antioxidant enzymes (SOD, POD and CAT), so the possibility that other antioxidants not studied here were activated could not excluded. In plants, PAs were found to play crucial roles not only in plant growth, physiology and reproduction, but also in conferring abiotic stress (salt, drought and metal/metalloid toxicity) tolerance by enhancing antioxidant defense and oxidative stress tolerance [21,41,55]. In this study, we observed a significant increase of PA content in OsHSFA3-overexpressing plants than in WT under both control as well as drought stress conditions ( Figure 6).…”
Section: Discussionsupporting
confidence: 54%
“…Further, we investigated only three key antioxidant enzymes (SOD, POD and CAT), so the possibility that other antioxidants not studied here were activated could not excluded. In plants, PAs were found to play crucial roles not only in plant growth, physiology and reproduction, but also in conferring abiotic stress (salt, drought and metal/metalloid toxicity) tolerance by enhancing antioxidant defense and oxidative stress tolerance [21,41,55]. In this study, we observed a significant increase of PA content in OsHSFA3-overexpressing plants than in WT under both control as well as drought stress conditions ( Figure 6).…”
Section: Discussionsupporting
confidence: 54%
“…From putrescine spermidine synthase produces spermidine, and spermine synthase synthesizes spermine from spermidine. Putrescine, spermidine and spermine are positively charged metabolites; therefore, they can bind to negatively charged compounds and neutralize ROS (Hasanuzzaman et al 2019 ). It cannot be excluded that enhanced activity of ARG in WCM plants can promote synthesis of polyamines and indirectly improve non-enzymatic antioxidant apparatus in these plants.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis and regulations of 2AP are largely affected by not only the genetic factors but also the external environment and crop management factors (Bao et al, 2018;Hasanuzzaman et al, 2019). The genetic factors play an important part in determining the quality of aromatic rice (Bao et al, 2018;Bradbury et al, 2008), which, on the other hand, are much dependent on prevailing environmental conditions during the growth period and also by pre-and postharvest management techniques (Gay et al, 2010).…”
mentioning
confidence: 99%